STUDI PEMANFAATAN JANTUNG PISANG DAN IKAN GABUS DALAM PEMBUATAN NUGGET - Lisma Pratiwi; Yusmarini '; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of research is to identify the ratio influence of the banana’s heart and the gabus fish concerning the result of nugget quality and the best formulation in making process of the banana’s heart and the gabus fish nugget. This research was carried out experimentally by using Completely Randomized Design consisting of 5 treatments with 3 replications. The treatments consist of JI1 = (banana’s heart 10 : gabus fish 90), JI2 = (banana’s heart 15 : gabus fish 85), JI3 = (banana’s heart 20 : gabus fish 80), JI4 = (banana’s heart 25 : gabus fish 75), JI5 = (banana’s heart 30 : gabus fish 70). Data optained were analyzed statistically using Anova and further tested with DNMRT at the level of 5%. The result of the research shows that the ratio of banana’s heart and gabus fish sausage significantly effect to the moisture content, ash content, protein content, fiber content, and sensory test. The best treatment on this research was nugget banana’s heart 15 : gabus fish 85, with moisture content of 32.80%, ash content 2.20%, protein content 15.19%, fiber content 1.78% and in terms of acceptable sensory by panelis. Keywords : Nugget, banana’s heart, gabus fish